Pengaruh Penambahan Probio dalam Pakan terhadap Bobot Hidup, Berat Karkas, Berat Dada, Berat Paha Atas dan Paha Bawah Ayam Broiler - Alexander Taek Nahak (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2019)
The purpose of this study was to determine the effect of adding probio in feed on live weight, carcass weight, breast weight, upper thigh weight, and lower thighs of broiler chickens. In this study 80 day old broiler chickens (DOC) were used. The method used was an experimental method with a completely randomized design (CRD) using 4 treatments and 4 replications. The treatments consisted of R0 = 100% commercial feed, R1 = 99.7% commercial feed + 0.3% probio, R2 = 99.5% commercial feed + 0.5% probio and R3 = 99.3% commercial feed + probio 0.7%. The results of analysis of variance showed that the use of probio in commercial feed had no significant effect on body weight, breast weight, upper thigh weight and lower thighs of broiler chickens but had a significant effect on carcass weight (P <0.05). The conclusion from the results of this study is that it can be concluded that the addition of probio in feed up to the level of 0.3% increases the weight of broiler chicken carcasses but does not affect the life weight, carcass percentage, weight and percentage of breast weight, percentage of thigh, upper thigh and lower thigh of broiler chickens at the age of 45 days.